HUBUNGAN PEMBERIAN ASI EKSLUSIF TERHADAP STATUS GIZI BAYI 6-12 BULAN WILAYAH KERJA PUSKESMAS PACCERAKKANG - Jumriani Jum; Henny Fauziah; Arlina Wiyata Gama (Universitas Islam Negeri Alauddin Makassar, 2022)
Breast milk is adequate food for infants in growth and development because its contents, such as nutrients and protective factors, play a role in increasing the speed of metabolism and growth to reduce infant morbidity and mortality. This study aimed to determine the relationship of exclusive breastfeeding to the nutritional status of infants aged 6-12 months in the Paccerakang Health Center Work Area. The method used is observational analytics with a retrospective approach. The sample in this study was taken using the purposive sampling method, which met the inclusion and exclusion criteria. The number of respondents was 50, while 25 respondents were taken from children who received exclusive breastfeeding and 25 who did not. Samples were taken using primary data from questionnaires and secondary data from medical records and then analyzed using the Chi-Square test with a significance level of 5% (α=0.05). The results of hypothesis testing using Chi-Square with a significance level of 5% (α=0.05), the p-value is 0.003 (P<0.05). This study's conclusion shows a relationship between a history of exclusive breastfeeding and the nutritional status of infants aged 6-12 months.